1995
DOI: 10.1254/jjp.67.279
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Tranilast on Pulmonary Fibrosis and Activation of Alveolar Macrophages in Mice Treated with Bleomycin: Role of Alveolar Macrophages in the Fibrosis

Abstract: ABSTRACT-We have reported that tranilast, an anti-allergic drug that inhibits chemical mediator release from mast cells, suppresses bleomycin (BLM)-induced pulmonary fibrosis in mice through mechanisms other than inhibiting chemical mediator release from mast cells. The purpose of this paper is to examine the effect of tranilast on alveolar macrophage (AM) activation and on the development of fibrosis in ICR mice instilled with BLM intratracheally. Twenty eight days after the BLM instillation (0.01 mg/mouse), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…It is already well known that tranilast has an inhibitory effect on the development of fibrosis (29,30), and in the two RA models in the present study, tranilast again showed its ability as an anti-fibrotic agent. However, the mechanism for this effect in these models remains unclear, especially with regards to the anti-inflammatory effects of tranilast.…”
Section: Discussionsupporting
confidence: 78%
“…It is already well known that tranilast has an inhibitory effect on the development of fibrosis (29,30), and in the two RA models in the present study, tranilast again showed its ability as an anti-fibrotic agent. However, the mechanism for this effect in these models remains unclear, especially with regards to the anti-inflammatory effects of tranilast.…”
Section: Discussionsupporting
confidence: 78%
“…Whole collagen content of the right lung was evaluated by determining hydroxyproline content [18]. Briefly, after recovery of BALF, the right lung lobes were removed and cut into sections (1 mm thick).…”
Section: Measurement Of Hydroxyproline Content In Right Lungsmentioning
confidence: 99%
“…Whole collagen content of the right lung was evaluated by determining hydroxyproline content [15]. Briefly, the right lung was cut into sections (1 mm thick).…”
Section: Measurement Of Hydroxyproline Content In Right Lungsmentioning
confidence: 99%